Analisis Dampak Dari Kerusakan pada Jalan Perhubungan, Tembung, Kecamatan Percut Sei Tuan Kabupaten Deli Serdang - Louis Armando Tarigan; Tulus Marco Diaztro; Widya Herliana Dewi Rambe; Winku Alvha Aripaga; Syuratty Astuti Rahayu Manalu (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Roads are infrastructure created as a facility for transportation activities to get to the place you want to go. Road damage has a significant impact on health, economy, safety and comfort. From the results of direct interviews, it was found that the impact of this road dredging was quite detrimental to the surrounding community but also brought a few benefits. damage that occurred along the Transportation Road, Tembung, Kec. Percut Sei Tuan, Deli Serdang Regency has not been paid attention to by the local government for a long time. The research results show that damage to transportation roads has caused various negative impacts on society. Mobility is hampered, causing increased travel time and transportation costs. Apart from that, traffic accidents are also increasing due to poor road conditions, threatening the safety of road users and even causing casualties. Road damage ultimately also affects the economy of the surrounding community. This journal uses qualitative research methods. Qualitative research method is a research method based on post-psychivism or interpretive philosophy, used to research the conditions of natural objects, where the researcher is the key instrument, data collection techniques are carried out by triangulation (a combination of observation, interviews, documentation).